Exploration of Fluid Physics Concepts into Local Wisdom Petik Laut Lamongan: Cultural and Scientific Perspectives - Novita Desysetyowati; Abd Kholiq (Jurnal Ilmiah Pendidikan Fisika, 2025)
Physics learning based on local wisdom integrates everyday phenomena directly into students' learning experiences, thereby creating a more meaningful physics teaching and learning process. Petik Laut is a tradition carried out by fishermen as a sign that they stop fishing during the west season because this condition is considered dangerous for fishermen, and as an expression of gratitude for the abundant sea products by throwing offerings into the sea. This Petik Laut tradition can be linked to the study of physics, especially fluids, because if we carry out a more in-depth analysis, this activity involves various physics concepts. Therefore, this research aims to explore the concept of fluid physics in the local wisdom of Petik Laut Lamongan. This research uses a qualitative research method that is oriented towards exploration with stages of data collection, data reduction, data display, and drawing conclusions. Data collection used three methods, namely observation, interviews, and documentation. Data will be analyzed descriptively. The results of the research show that the physics concepts contained in the local wisdom of Petik Laut Lamongan are three physical concepts that can be explored, namely Bernoulli's Law, Archimedes' Law, and hydrostatic pressure. In practice, these findings can be used as a source of material for the development of media and learning resources based on local wisdom, which not only enrich physics teaching materials but also encourage cultural preservation through integration into the education curriculum.